Development of Practicum Instruction Module Based on Project Based Learning (PjBL) Integrated with Science Process Skills and Scientific Literacy - Marjanah Marjanah; Ekariana Pandia; Nursamsu Nursamsu (Jurnal Penelitian Pendidikan IPA, 2021)
This research aims to produce a valid practicum instruction module; the result of student assessments regarding the practicum instruction module; there are good results of students’ scientific process skills; there is an increase in students' scientific literacy; and student responses to the practicum instruction module. This type of research refers to the 4-D model. The research subjects are Even Semester students for the 2020-2021 academic year. The research was carried out at the Biology Education Study Program, Universitas Samudra. The research instrument consisted of validation sheets, observation sheets, test questions, and questionnaires. The data analysis technique in this study consisted of validation data presented in the form of a percentage; student assessment of the practicum instruction module using percentages process skills data analyzed by N-gain score; learning outcomes were analyzed by N-gain score, and; student responses are presented in the form of a percentage. The results of the practicum module validation are categorized as good with a score of 87.5%; The results of student assessment of the practicum instruction module on product trials are categorized as good in terms of indicators of content feasibility, presentation feasibility, and language; The scientific process skills of students before and after conducting product trials of 0.63% are categorized as high; The scientific literacy ability of students is 0.56%, means it has increased; Student response to the practicum Instruction module is positive